Quality of life in the climacteric - Ayala Peralta, Félix (2015)
OBJETIVE: To determine the quality of life of climacteric patients. DESIGN: Prospective descriptive study, survey type. PLACE: Menopause Unit of the Specialized Maternal Perinatal Institute of Lima, in 2002. MATERIAL AND METHODS: One hundred and ten new climacteric patients were surveyed by Hiditch test. RESULTS: 52% were comprised between 45 and 54 years old; 49% are natural posmenoausea. The most common symptoms were anxiety or nervousness in 89% (98 cases), musculoskeletal pain 90% (98), depression in 83% (92) and headache in 79% (87). When applying logistic regression it was observed that the loss of quality of life in these women are mainly in the physical psychosocial areas (4.64 ± 1.52) and (4.14 ± 1.32) and does not depend on age or sociodemographic variables, but essentially to be in menopause. CONCLUSION: The questionnaire Hiditch suggests that there is a considerable deterioration in the quality of life of climacteric women, which seems to depend mainly of estrogen deficiency.